PENILAIAN KINERJA KEUANGAN LPD DESA PAKRAMAN ISEH MENGGUNAKAN METODE BALANCED SCORECARD - Kusuma, I Komang Budi; Nuryani, Ni Nyoman Juli (Jurnal Daya Saing, 2023)
The purpose of this study was to determine the financial performance of LPDIseh Village using the Balanced Scorecard method. This research uses qualitative andquantitative methods. The data collection techniques used in this study were interviewsand documentation, in which the chairmen and employees of the Iseh Village LPD wereused as respondents. The data analysis technique used in this research is descriptivequantitative. Based on the results of research on the financial perspective starting fromthe ratio of capital, liquidity, and profitability can be categorized as healthy according tothe valuation standards. From a customer perspective, as measured by acquisition,retention and profitability, customers can be categorized as healthy. In the perspective ofinternal business processes measured by the interview method can be categorized ashealthy. And from the perspective of learning and growth as measured by HumanResources (HR), technology systems and company procedures can be categorized ashealthy.